ANALISIS YURIDIS TERHADAP PERMOHONAN PEMBATALAN AKTA HIBAH YANG DITOLAK MELALUI PUTUSAN PENGADILAN NEGERI SLEMAN NOMOR 09/PDT.G/2009/PN.SLMN - , DESI RATNANINGRUM, Dr. Tata Wijayanta, S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is aimed at analyzing the Verdict of Sleman District Court Number 09/Pdt.G/2009/PN.Slmn which rejects the Petition for the Annulment of the Deed of Donation Number 10/2006, analyzing the compliance of the verdict with the provision of the Civil Code, and analyzing the validity of the Deed of Donation Number 10/2006. This research is a juridical-normative research, which employed secondary data through a library research grounded on primary law materials, secondary law materials and tertiary law materials. Data were collected through a documentary method by means of documentary study. The obtained data were analyzed qualitatively with descriptive method. The research result indicates the Deed of Donation Number 10/2006 which had been donated could not be annulled by the donor because it was proven valid and not legally defective. The court considered the annulment of donation rejected because the plaintiff failed to prove his arguments from written evidence and witness evidence which were brought to the trial and connected with provisions in the Civil Code, namely Article 1666 of the Civil Code, Article 1672 of the Civil Code and Article 1688 of the Civil Code, that there was no fact that could be used as the basis of annulling the donation, which had been conducted by the plaintiff to the defendant. Therefore, the court decided to reject the claim of the plaintiff. It can be concluded from the research result that the petition of annulment of the Deed of Donation Number 10/2006 was rejected because according to the court the requirements of donation annulment in Article 1672 of the Civil Code and Article 1688 of the Civil Code was not fulfilled and the Plaintiff failed to prove his arguments, so that the Deed of Donation Number 10/2006 was declared valid, and the verdict of the rejection on the petition of donation annulment had complied with the provision in the Civil Code. Therefore, it is suggested that the donor should know all of the consequences of giving donation. The donor should be careful in calculating and considering his own property before determining the property which will be donated so as to avoid disputes in the future.